Magnetically responsive layer-by-layer microcapsules can be retained in cells and under flow conditions to promote local drug release without triggering ROS production. Issue 14 (25th March 2020) - Read, Jordan E.; Luo, Dong; Chowdhury, Tina T.; Flower, Rod J.; Poston, Robin N.; Sukhorukov, Gleb B.; Gould, David J.
Abstract : Magnetically responsive LbL microcapsules are biologically inert, magnetically retained in flow and cell migration assays so are retainable drug delivery vehicles. Abstract : Nanoengineered vehicles have the potential to deliver cargo drugs directly to disease sites, but can potentially be cleared by immune system cells or lymphatic drainage. In this study we explore the use of magnetism to hold responsive particles at a delivery site, by incorporation of superparamagnetic iron oxide nanoparticles (SPIONs) into layer-by-layer (LbL) microcapsules. Microcapsules with SPIONs were rapidly phagocytosed by cells but did not trigger cellular ROS synthesis within 24 hours of delivery nor affect cell viability. In a non-directional cell migration assay, SPION containing microcapsules significantly inhibited movement of phagocytosing cells when placed in a magnetic field. Similarly, under flow conditions, a magnetic field retained SPION containing microcapsules at a physiologic wall shear stress of 0.751 dyne cm −2 . Even when the SPION content was reduced to 20%, the majority of microcapsules were still retained. Dexamethasone microcrystals were synthesised by solvent evaporation and underwent LbL encapsulation with inclusion of a SPION layer. Despite a lower iron to volume content of these structures compared to microcapsules, they were also retained under shear stress conditions and displayed prolonged release of active drug, beyond 30 hours, measured using a glucocorticoid sensitive reporter cell line generated in this study. Our observations suggest use of SPIONs for magnetic retention of LbL structures is both feasible and biocompatible and has potential application for improved local drug delivery.